Crystal structures of Val58Ile tryptophan repressor in a domain‐swapped array in the presence and absence of l‐tryptophan. Issue 7 (30th June 2021) - Sprenger, Janina; Lawson, Catherine L.; von Wachenfeldt, Claes; Lo Leggio, Leila; Carey, Jannette
Abstract : In a domain‐swapped, gel‐like crystalline form of Escherichia coli tryptophan repressor, the physiological ligand l ‐tryptophan binds equivalently as in the native dimeric repressor, even though the binding‐site residues originate from three distinct polypeptide chains instead of two, and large solvent channels accommodate a disordered N‐terminal extension. Proteins that cannot otherwise be crystallized might be oriented in the channels for diffraction analysis by exploiting these features. Abstract : The crystal structures of domain‐swapped tryptophan repressor (TrpR) variant Val58Ile before and after soaking with the physiological ligand l ‐tryptophan (l ‐Trp) indicate that l ‐Trp occupies the same location in the domain‐swapped form as in native dimeric TrpR and makes equivalent residue contacts. This result is unexpected because the ligand binding‐site residues arise from three separate polypeptide chains in the domain‐swapped form. This work represents the first published structure of a domain‐swapped form of TrpR with l ‐Trp bound. The presented structures also show that the protein amino‐terminus, whether or not it bears a disordered extension of about 20 residues, is accessible in the large solvent channels of the domain‐swapped crystal form, as in the structures reported previously in this form for TrpR without N‐terminal extensions. These findings inspire the exploration of l ‐Trp analogs and N‐terminal modifications as labels to orient guest proteins that cannot otherwise be crystallized in the solvent channels of crystalline domain‐swapped TrpR hosts for potential diffraction analysis.